Leadership in Action : In Focus - Leading Through Transitions - A Kinder, Gentler, and Better Way to Downsize - Yacabucci, Nick (Center for Creative Leadership, 2005)
Organizations can avoid the destructiveness of downsizing while accomplishing the objectives that prompted the reduction and even doing some good in the process.